Development of small/medium size no-till and minimum-till seeders in Asia: A review - Jin, He; Zhiqiang, Zhang; Hongwen, Li; Qingjie, Wang (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: The benefits of conservation agriculture (CA), have been widely recognized and CA has been widely adopted in many parts of the world. However, there are some factors that limit the widespread adoption of CA in Asia. The most prominent factor appears to be the lack of suitable CA seeders for small to medium sized land-holding (SLH) farmers. This paper summarizes the small to medium no-till and minimum-till seeders currently available in Asia, and classifies these seeders into four types: manually operated units, animal traction seeders, two-wheel tractor and four-wheel tractor driven seeders. Detailed characteristics have been provided for some typical CA seeders and comparisons were made as to their suitability under particular working conditions. Typically manual and animal traction seeders are confined to small farms and hilly areas, while the larger CA seeders suited to four-wheel tractors are used on larger acreages. To ensure seeding performance on most four-wheel tractor CA seeders, two types of anti-blocking mechanisms (passive and active anti-blocking) have been fitted. Finally, the paper proposes a future direction and development of CA seeders for small/medium size farms in Asia, and also suggests changes in policy support, improvement of anti-blocking mechanisms, suitability for various crops, geographical zones and the contribution of development by public private partnerships to advance the adoption of CA seeders. Keywords: Conservation Agriculture (CA), conservation tillage, no-till, minimum-till, seeder, tractor, anti-blockage, Asia DOI: 10.3965/j.ijabe.20140704.001 Citation: He J, Zhang Z Q, Li H W, Wang Q J. Development of small/medium size no-till and minimum-till seeders in Asia: A review. Int J Agric & Biol Eng, 2014; 7(4): 1-12.